First Report of an Emerging Ulcerative Skin Disease in Invasive Lionfish - Holden Earl Harris; Alexander Q. Fogg; Roy P. Yanong; Salvatore Frasca Jr; Theresa Cody; Thomas B. Waltzek; William F. Patterson (EDIS, 2018)
An emerging ulcerative skin disease in invasive lionfish in Florida and Caribbean Sea is being tracked. Diseased lionfish were first reported in summer 2017 from the northern Gulf of Mexico with additional reports in 2018. Florida Fish and Wildlife Conservation Commission,  University of Florida, and other fish health scientists are investigating this disease, but initial evaluations have not yet identified a cause.  More advanced diagnostics are underway to better understand the factors causing this disease/syndrome and its potential to spread to other species. Researchers are also examining the lethal and chronic effects of this disease on individual fish, as well as its effect on lionfish populations, the lionfish fishery, and reef fish communities. Researchers and Extension Personnel (IFAS/SeaGrant) are asking stakeholders to report and document any ulcerated or otherwise diseased lionfish in FL and the Caribbean.